Low overpotential high activity manganese/ruthenium mixed oxide electrocatalysts for oxygen evolution in alkaline media. - Lyons, Michael; Colavita, Paula; Browne, Michelle (My University, 2015)
The combination of a platinum group material (i.e. ruthenium) with a first row transition metal (i.e. manganese) could provide stability and lower the cost of OER electrocatalyst, while still obtaining good OER properties. In this work classical electrochemical techniques have been used to study the electrocatalytic properties of thermally prepared manganese, mixed manganese/ruthenium and ruthenium based electrocatalysts on a titanium substrate at three different annealing temperatures for OER. The structure and morphology of the thermally decomposed oxide materials are examined using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) spectroscopy. Turnover Frequency (TOF) numbers are also calculated. The initial OER overpotential values of eight electrocatalysts, in this study, are lower than that of the lowest known OER electrocatalyst, RuO 2 . All SEM images with 10 – 100 % of RuO x show a mud-cracked morphology. This morphology is attributed to the excellent electrocatalytic activity of RuO 2
PUBLISHED
Keywords: Nanoscience & Materials; Catalysis; Nanochemistry